Catholic Vietnam: a church from empire to nation - Keith, Charles (From Indochina to Vietnam, 2012)
A church between the Nguyẽ̂n and the French -- A colonial church divided -- The birth of a national church -- Vietnamese Catholic tradition on trial -- A national church experienced -- The culture and politics of Vietnamese Catholic nationalism -- A national church in revolution and war -- Epilogue : a national church divided